Conditional proxy broadcast re-encryption with fine grain policy for cloud data sharing. (2019) - Sun, Maosheng; Ge, Chunpeng; Fang, Liming; Wang, Jiandong
Conditional proxy broadcast re-encryption (CPBRE) enables a semi-trusted proxy to convert Alice's ciphertext satisfying a certain condition into a set of users' ciphertext. The proxy, however, cannot learn anything about the underlying plaintext. The traditional CPBRE schemes cannot support flexible control on conditions. In this paper, we present a new primitive named conditional proxy broadcast re-encryption with fine grain policy (CPBRE-FG). In a CPBRE-FG scheme, the re-encryption key is generated with an access tree, and the ciphertext is constructed under a set of descriptive conditions. The proxy can convert a ciphertext if and only if the set of conditions satisfies the access tree. We formalise the notion of CPBRE-FG and present an efficient CPBRE-FG scheme. Finally, we prove it against chosen-ciphertext attack (CCA) security in the random oracle model.